Uji Efektivitas Perasan Daun Beluntas (Pluchea indica) Terhadap Mortalitas Rayap Tanah (Coptotermes curvignathus): TEST THE EFFECTIVENESS OF BELUNTAS LEAF EXTRACT (Pluchea indica) AGAINST MORTALITY OF SUBTERRANEAN TERMITES (Coptotermes curvignathus) - Saputri, Rizki Dwi; Djuniwati Lisminingsih, Ratna; Zayadi, Hasan (Jurnal SAINS ALAMI (Known Nature), 2024)
Subterranean termites are a type of termite that can cause damage to buildings made of wood. The bioactive content of beluntas leaves has the potential as a vegetable pesticide that can kill termites. Research has been carried out to determine the effect and effective concentration of beluntas leaf juice on the LC50 value, as well as the effect of abiotic factors on the mortality of subterranean termites. The parameters of this study were termite mortality after being given treatment and measuring abiotic factors during the study. This study used a completely randomized design (CRD) with 2 stages of testing, a preliminary test and a definitive test. The abiotic factor parameters measured were air temperature, air humidity, soil moisture, and light intensity. The definitive test to get the LC50 used 4 treatments, namely 0%, 40%, 63%, and 100%, the concentration according to the results of the logarithm calculation from the results of the preliminary test. Observations were carried out every 24 hours for 72 hours. Data were analyzed using probit analysis as well as ANOVA test and chi-square test for abiotic factor parameters. The results of the probit analysis test showed that the LC50-24 hours was 48%, the LC50-48 hours was 23.75% and the LC50-72 hours was 12.74%. The results of the ANOVA test showed that there were significant differences in the mortality of subterranean termites after being treated with concentrations of 0%, 40%, 50%, and 100%. The most effective concentration is 100% concentration. The effective concentration of beluntas leaf juice (Pluchea indica) can kill 50% of subterranean termites for 24, 48 and 72 hours, namely LC50-24 hours is 40%, LC50-48 hours is 23.75%, LC50-72 hours is 12.74 %. Keywords: Beluntas Leaves (Pluchea indica), Mortality, Subterranean Termites (Coptotermes curvignathus)   ABSTRAK Rayap tanah merupakan jenis rayap yang dapat menyebabkan kerusakan pada bangunan yang berbahan dasar kayu. Kandungan bioaktif daun beluntas berpotensi sebagai pestisida nabati yang dapat membunuh rayap. Telah dilakukan penelitian yang bertujuan untuk mengetahui pengaruh dan kosentrasi efektif perasan daun beluntas nilai LC50, serta pengaruh faktor abiotik terhadap mortalitas rayap tanah. Parameter penelitian ini yakni mortalitas rayap setelah diberikan perlakuan serta mengukur faktor abiotik selama penelitian. Penelitian ini menggunakan Rancangan Acak Lengkap (RAL) dengan 2 tahap pengujian, uji pendahuluan dan uji definitif. Parameter faktor abiotik yang diukur yakni suhu udara, kelembapan udara, kelembapan tanah, dan intensitas cahaya. Uji definitif untuk mendapatkan LC50 menggunakan 4 perlakuan yaitu 0%, 40%, 63%, dan 100%, kosentrasi sesuai hasil perhitungan logaritma dari hasil uji pendahuluan. Durasi pengamatan dilakukan setiap 24 jam selama 72 jam. Data dianalisis dengan menggunakan analisis probit serta uji ANOVA dan uji chi-square untuk parameter faktor abiotik. Hasil uji analisis probit menunjukkan menunjukkan nilai LC50-24 jam adalah 48%, LC50-48 jam adalah 23,75% dan LC-72 jam sebesar 12,74 %. Hasil uji ANOVA menunjukkan bahwa terdapat perbedaan yang signfikan mortalitas rayap tanah setelah diberi perlakuan kosetrasi 0%, 40%, 50%, dan 100%. Kosentrasi yang paling efektif dalam mempengaruhi mortalitas rayap tanah yaitu kosentrasi 100%. Kata kunci: Daun Beluntas (Pluchea indica), Mortalitas, Rayap Tanah (Coptotermes curvignathus)